2010
DOI: 10.1094/phyto-100-9-0949
|View full text |Cite
|
Sign up to set email alerts
|

Early Events of Citrus Greening (Huanglongbing) Disease Development at the Ultrastructural Level

Abstract: Citrus greening (Huanglongbing [HLB]) is one of the most destructive diseases of citrus worldwide. The causal agent of HLB in Florida is thought to be 'Candidatus Liberibacter asiaticus'. Understanding of the early events in HLB infection is critical for the development of effective measures to control the disease. In this work, we conducted cytopathological studies by following the development of the disease in citrus trees graft inoculated with 'Ca. L. asiaticus'-containing material under greenhouse conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
153
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 18 publications
12
153
0
11
Order By: Relevance
“…The asymptomatic flush become symptomatic due to an increase in concentration of the pathogen, making the symptomatic flush more infectious to vectors than the asymptomatic flush (22). In one study more active bacterial cells were observed in presymptomatic than in highly symptomatic leaf samples (23), suggesting that the bacteria are dormant or dead in highly symptomatic tissue. However, a positive correlation between concentration of CLas and HLB symptom expression has also been shown (22).…”
Section: Methods and Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The asymptomatic flush become symptomatic due to an increase in concentration of the pathogen, making the symptomatic flush more infectious to vectors than the asymptomatic flush (22). In one study more active bacterial cells were observed in presymptomatic than in highly symptomatic leaf samples (23), suggesting that the bacteria are dormant or dead in highly symptomatic tissue. However, a positive correlation between concentration of CLas and HLB symptom expression has also been shown (22).…”
Section: Methods and Resultsmentioning
confidence: 96%
“…(iv) Symptomatic flush is assumed to be more infectious than asymptomatic flush on the basis of higher CLas DNA densities in symptomatic flush (22). Recently, large numbers of active CLas cells were found in tissue samples from presymptomatic young flushes whereas more inactive bacteria were observed in highly symptomatic samples (23). If we assume that the symptomatic flush is less infectious than the asymptomatic one, then the number of subsequent infections will be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations